2016
DOI: 10.1016/j.nucengdes.2015.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Time-domain soil-structure interaction analysis of nuclear facilities

Abstract: The Nuclear Regulatory Commission (NRC) regulation 10 CFR Part 50 Appendix S requires consideration of soil-structure interaction (SSI) in nuclear power plant (NPP) analysis and design. Soil-structure interaction analysis for NPPs is routinely carried out using guidance provided in the ASCE Standard 4 titled "Seismic Analysis of Safety-Related Nuclear Structures and Commentary (ASCE-4, 1998)". This document, which is currently under revision, provides detailed guidance on linear seismic soil-structure-interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(29 citation statements)
references
References 10 publications
1
28
0
Order By: Relevance
“…Notably, the original design value in Fukushima was 0.26g (updated to 0.45g in 2009), while the recorded one was 0.56g. Similar exceedances have also been reported (Coleman et al, 2015) elsewhere in Japan (e.g., Kashiwazaki-Karina, 0.20g versus 0.32g recorded) and the United States (at the 1,865-MW North Anna Power Station in Mineral, Va, 0.18g versus 0.26g recorded in 2011 during a magnitude 5.8 event). In fact, the latter event was the only time an earthquake has forced a U.S. nuclear plant offline and also the first U.S. plant to experience an event that exceeded its design acceleration (within a time window of three seconds).…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…Notably, the original design value in Fukushima was 0.26g (updated to 0.45g in 2009), while the recorded one was 0.56g. Similar exceedances have also been reported (Coleman et al, 2015) elsewhere in Japan (e.g., Kashiwazaki-Karina, 0.20g versus 0.32g recorded) and the United States (at the 1,865-MW North Anna Power Station in Mineral, Va, 0.18g versus 0.26g recorded in 2011 during a magnitude 5.8 event). In fact, the latter event was the only time an earthquake has forced a U.S. nuclear plant offline and also the first U.S. plant to experience an event that exceeded its design acceleration (within a time window of three seconds).…”
Section: Introductionsupporting
confidence: 83%
“…Other studies have further demonstrated a thorough non-linear SSI methodology for NPP constructions in the time domain, incorporating the presence of material (Kabanda et al, 2015) and geometrically nonlinearities (Coleman et al, 2015;Huang et al, 2010) at the soil-foundation interface, such as gapping and sliding. All these studies highlight the potentially significant impact of nonlinear phenomena, particularly for ground intensities exceeding the Design Basis Earthquake.…”
Section: Introductionmentioning
confidence: 99%
“…30,31 Examples of this approach include Elgamal et al, 32 Ostadan et al, 33 and Coleman et al 34 to name a few. 30,31 Examples of this approach include Elgamal et al, 32 Ostadan et al, 33 and Coleman et al 34 to name a few.…”
Section: Introductionmentioning
confidence: 99%
“…A more "classical" approach to seismic SSI involves inputing the (1-D) wave field as a stress input at a given depth under the model and capturing out-going motions with Lysmer-type boundaries. 30,31 Examples of this approach include Elgamal et al, 32 Ostadan et al, 33 and Coleman et al 34 to name a few.…”
Section: Introductionmentioning
confidence: 99%
“…The assumption of equivalent linear behavior does not explicitly consider the nonlinear behavior of soil-structure systems such as the hysteretic behavior of soil. In the time domain analysis method [2][3][4][5][6] , the dynamic analysis is carried out by solving the equation of motion at each time step using a direct numerical integration scheme. In this approach, a large soil domain and a structural system is modeled as a single numerical model such that the inertial and kinematic interactions are inherently considered in the analysis.…”
Section: Introductionmentioning
confidence: 99%